Pengaruh Harga, Kualitas Produk, Kualitas Layanan Dan Lokasi Terhadap Keputusan Pembelian (Studi Kasus Pada Pelanggan Kedai AJ Coffee Sidayu di Kota Gresik) - Rizqi Adi Saputra; Agus Widarko; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract Based on research conducted with the aim of analyzing the effect of Price, Product Quality, Service Quality and Loaction on Purchase Decisions at AJ Coffee Sidayu’s Customers in Gresik city. The population in this study were the customers of Kedai AJ Coffe Sidayu totaling 110 people. The sampling technique used is random sampling where every customer in the population has the opportunity to be a sample. The analytical method used in thes research is multipe linear regression analysis with hypothesis testing using t test and f test. From this study, it was found that the price variable partially influences the  purchasing decision, but the product quality, service quality and location variables have no effecton purchasing decisions. Meanwhile, the variables of price, product quality, service quality and location simultaneously affect purchasing decisions. Keywords: Price, Product Quality, Service Quality, Location, Purchase Decision.